Methylene Bridging Effect on the Structures, Lewis Acidities and Optical Properties of Semi‐planar Triarylboranes. Issue 5 (8th December 2020) - Doan, Thu‐Hong; Chardon, Aurélien; Osi, Arnaud; Mahaut, Damien; Tumanov, Nikolay; Wouters, Johan; Champagne, Benoît; Berionni, Guillaume
Abstract: Three synthetic methods towards semi‐planar triarylboranes with two aryl rings connected by a methylene bridge have been developed. The fine‐tuning of their stereoelectronic properties and Lewis acidities was achieved by introducing fluorine, methyl, methoxy, n ‐butyl and phenyl groups either at their exocyclic or bridged aryl rings. X‐ray diffraction analysis and quantum‐chemical calculations provided quantitative information on the structural distortion experienced by the near planar hydro‐boraanthracene skeleton during the association with Lewis bases such as NH3 and F − . Though the methylene bridge between the ortho ‐positions of two aryl rings of triarylboranes decreased the Gibbs free energies of complexation with small Lewis bases by less than 5 kJ mol −1 relative to the classical Lewis acid BAr3, the steric shielding of the CH2 bridge is sufficient to avoid the formation of Lewis adducts with larger Lewis bases such as triarylphosphines. A newly synthesized spirocyclic amino‐borane with a long intramolecular B−N bond that could be dissociated under thermal process, UV‐irradiation, or acidic conditions might be a potential candidate in Lewis pairs catalysis. Abstract : A series of semi‐planar triarylboranes were obtained by three procedures. The effects of the planarization induced by the methylene bridge on their steric shielding, Lewis acidities and optical properties were investigated by experiments and quantum chemical calculations. These methods can be extended to the preparation of functionalized spirocyclic amine‐boranes and unsymmetrical triarylboranes, which might be used in frustrated Lewis pair chemistry or as pH and photo‐responsive boron Lewis acids.